THE EFFECT OF SEVIMA EDLINK'S E-LEARNING ASSISTED GUIDED INQUIRY MODEL ON STUDENT LEARNING OUTCOMES IN SOUND WAVES MATERIAL IN CLASS XI SMA MASEHI GBKP BERASTAGI T.P 2022/2023 - Ginting, Noperanta; Motlan, Motlan (UNIVERSITAS NEGERI MEDAN, 2023)
This study aims to determine the effect of Sevima Edlink's e-learning-assisted guided inquiry model on high school students™ physics learning outcomes in sound wave material. This research is a type of quasi-experimental research with a two-group pretest-posttest design. The population in this study were all XI MIPA classes at Masehi High School, GBKP Berastagi T.P 2022/2023 and the samples in this study were class XI MIPA 2 (experimental class) and XI MIPA 1 (control class) which were taken by cluster random sampling. The instrument used was a multiple-choice test with 15 questions. The results showed that the average pretest and posttest scores in the experimental class were 36.23 and 80.89. While in the control class were 34.86 and 75.63. Data analysis was carried out by t-test with a significant level of Î± = 0.05, it was found that tcalculated < ttable = (2.286 > 1.669) then H0 was rejected and Ha was accepted, which means that there is a significant influence of the guided inquiry model assisted by the e-learning sevima edlink on learning outcomes students in class XI SMA Swasta Massehi GBKP Berastagi on sound waves material.